2015
DOI: 10.5539/ibr.v8n5p120
|View full text |Cite
|
Sign up to set email alerts
|

The Conception of Street Vending Business (SVB) in Income Poverty Reduction in Tanzania

Abstract: Street vending is ubiquitous, especially in developing countries. Despite its role in pro-poor economies, it has received little attention; much has been focused on its negative impacts like, use of public space, congestion, health and safety risks, tax evasion and the sale of shoddy merchandise. In Tanzania, street traders are usually concerned with confrontation with local authorities, and at the end they lose their products and money. This study is basically concerned with exploring the approaches of street… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…In many developing countries, the street food trade is considered a part of the informal economy and represents a regular source of income and employment for urban populations. Also, the street vending business can represent an alternative to the saturated formal sector, ensuring a source of supplemental income from other activities, as earlier studies have revealed [35,36]. According to previous studies, one of the main motivating factors to engage in street vending activity is a lack of employment [37,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many developing countries, the street food trade is considered a part of the informal economy and represents a regular source of income and employment for urban populations. Also, the street vending business can represent an alternative to the saturated formal sector, ensuring a source of supplemental income from other activities, as earlier studies have revealed [35,36]. According to previous studies, one of the main motivating factors to engage in street vending activity is a lack of employment [37,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, half of the vendors reported to had invested at least R$ 50,000 (US$ 12,000) to enter the FT sector, and almost all owned the FT they worked at ( n = 34). Contrarily, SF activity in low- and middle-income countries constitutes a major source of income and employment for the poor, with vendors usually experiencing low average earnings, which makes street vending in those locations an unprofitable activity [21,35,36,37,38,40,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, local governments repress and control street vending activities (Njaya, 2014;Rogerson, 2016). Solutions to street vending challenges do not reside only in street vendors' representatives and local authorities, but the central government should also be a significant player since political leaders have to achieve economic sustainability through poverty reduction (Mramba, 2015).…”
Section: Street Vending Governance In Zimbabwementioning
confidence: 99%
“…Many use a doorway as a place of business. Mramba (2015) explained that in Tanzania, the mode of operation varies from vendor to vendor, depending on the type of product sold. Products are carried and displayed on tables, carts, bicycles and baskets, and carried by hand, on the shoulder, or by using containers built from boxes and burlap bags.…”
Section: Socioeconomic Characteristicsmentioning
confidence: 99%